Morphological review of the order Neelipleona (Collembola) through the redescription of the type species of Acanthoneelidus, Neelides and Neelus - Schneider, Clément (Zootaxa, 2017)
This work proposes a comprehensive review of the morphological features of the Neelipleona, with focus on chaetotaxy. The major contributions to the knowledge of Neelipleona are discussed and new data are presented, acquired from the redescription of Neelides folsomi, Acanthoneelidus pratensis and Neelus murinus. New elements of description are given for Neelus fimbriatus, Megalothorax granulosus, Megalothorax minimus, Megalothorax nigropunctatus, Megalothorax svalbardensis. Juvenile morphology is also taken in consideration with the description of the early instar of Neelides folsomi, Neelus murinus, Megalothorax minimus and Megalothorax nigropunctatus. A nomenclatural framework is proposed to illustrate the descriptions and the hypotheses of homology debated in the paper. Comparative tables are provided to summarize the morphological variations observed in the order. An identification key to the genera is also provided. A set of intriguing and unique characteristics of the Neelipleona were discovered or enlighten such as labral morphology, vibrating antennae in the genus Neelus, special chaetae associated to the secretion of wax rods and pattern of special τ-chaetae.Printed copy of this book is available from US$30.8 plus postage, Click here to order.